2020
DOI: 10.1088/1755-1315/445/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Gender issues and women’s participation in agricultural production in Warri South Local Government area of Delta State, Nigeria

Abstract: Gender inequality of women participation in agricultural production has become a worrisome discussion in the present dispensation. This is because women constitute large portion in agriculture business. The study therefore examines this issue, stressing on the extent of women’s participation in agriculture. The highest frequency of women that engage in farming all year round is 48 (30.0%), 44 (27.6%) respondents engage in farming activities half a year, 35 (21.8%) engage quarterly in a year. While cultural pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
2
5
0
Order By: Relevance
“…The participation of more women in the survey could be as a result of the fact that fertility is a pride commodity celebrated as “Ewu Ukwu” for women who have given birth to ten children in the community. This is also consistent with the findings of Asamu et al. (2020) .…”
Section: Presentation and Discussion Of Resultssupporting
confidence: 93%
“…The participation of more women in the survey could be as a result of the fact that fertility is a pride commodity celebrated as “Ewu Ukwu” for women who have given birth to ten children in the community. This is also consistent with the findings of Asamu et al. (2020) .…”
Section: Presentation and Discussion Of Resultssupporting
confidence: 93%
“…"This confirm such because there were few challenges women encounter such as land acquisition, problem of loans, aids and grants. The findings further affirm that indeed, women to a large extent are sidelined as a result of cultural norms and values of the society" [17]. "But this was in stark contrast to a study which highlights the high level of physical involvement by women in agricultural activities in Vanuatu [18].…”
Section: Resultsmentioning
confidence: 49%
“…The most recent data reported by Eurostat suggests that, on the average, 29% of farms across the EU are managed by a woman [16]. While it was noted that the number of women in farming is increasing, a previous research study found that women's participation in agricultural production is not high to a large extent such as that in Nigeria [17]. "This confirm such because there were few challenges women encounter such as land acquisition, problem of loans, aids and grants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst there are some success stories of women's empowerment, there are also examples of fundamentally structural causes of inequality impeding success. In Nigeria, women's year-round participation in agricultural production in the Warri South Local Government Area was only around 30%, with cultural norms of patriarchy forming the major barrier (Asamu et al, 2020). In Niger, women's lack of security of land tenure remained a significant barrier to agricultural production (Issoufou et al, 2020).…”
Section: ) Moreover Gender-blind Interventions Can End Upmentioning
confidence: 99%